Instructional leadership practices of selected principals in Maldives - a case study - Abdulla, Rasheed Ahmed (2016)
Instructional leadership has taken central place as a successful model to be practised by principals in leading schools. There was no research yet to explore the extent to which school principals in Maldives are adopting this model. Hence this research attempts to investigate the instructional leadership practices of selected principals in Maldives. Due to the exploratory requirement of the research, a qualitative methodology was employed using a multi-case study where data was collected through an in-depth semi-structured individual interviews utilising purposeful sampling method. Triangulation was adopted through multiple data sources such as observations, and written documents in order to support and enrich the findings. Participants of this study included three principals, three supervisors and three teachers from three selected schools. The study used a revised instructional leadership behaviour model of Hallinger and Murphy (1990) to analyze the data using within and across cases thematic approach. The findings of this study revealed that principals practiced the six dimensions of the instructional leadership behaviors and patterns as highlighted in the conceptual framework. However, from the across analysis case study, the study revealed that a) although all schools have mission and vision to provide proper direction but they are not clear whether to promote learning or to prepare for examination and b) community is not involved in designing vision and mission c) there was also confusion in the role of principals as an instructional or administrative leadership, d) no professional standards formulated for instructional leaders, e) a policy is needed for effective integration of ICT in teaching and learning, f)important behaviours of principals as instructional leaders include interaction with students and direct involvement in instruction and evaluation and g) provide holistic education for overall development and also an effective learning environment, As for barriers to be instructional leaders, the study showed lack of professional development, policies from Ministry of Education and high expectations from public. This study concluded that the revised model may be used as a guide to promote the instructional leadership behaviors and patterns among the principals in the Maldives. The revised model is considered as the contribution of this study.